"We never boil our milk, it will cause sore udders and mastitis in our cows"- consumption practices, knowledge and milk safety awareness in Senegal - Bhagyalakshmi Chengat Prakashbabu; Jacqueline M. Cardwell; Laura Craighead; Andrée Prisca Ndjoug Ndour; Damitoti Yempabou; Elhadji Ba; Rianatou Bada-Alambedji; Ayayi Justin Akakpo; Javier Guitian (BMC, 2020)
Abstract Background Milk is a nutrient-rich food that makes an important contribution to diets in several Low and Middle Income Countries such as Senegal. Milk can also harbour several pathogenic microorganisms. As in other low and middle income countries, the dairy industry in Senegal is growing, with an expansion of farms to meet rapidly growing demand in the cities. However, most of the production still happens in the informal sector, and little is known about consumption of milk and milk products, or knowledge, awareness and practices of actors in informal dairy supply chains. Methods We conducted structured focus group discussions with dairy farmers and milk processors in three selected regions (Dakar, Thies and Fatick) in Senegal to investigate the consumption practices, awareness of milk borne hazards, and practices relevant to the risk of milk contamination to gain a deeper understanding of drivers of milk-borne diseases. Data on the consumption of milk and milk products were also collected using a closed questionnaire. Results Results indicate that milk is an important part of the diet in the study regionsand raw milk consumption is very common. The most common milk product consumed was fermented milk. Awareness of milk borne hazards was limited. Several farmers and processors reported risky practices, despite being aware of better practices, due to cultural beliefs. In households, children, pregnant women and older people were prioritised when milk and milk products were distributed. Dairy farmers and milk processors were more concerned with the lack of food for animals, low production and seasonality of production than the safety of the milk and milk products. Conclusions Lack of awareness of milk borne infections and some traditional practices put milk and milk product consumers in the study area at high risk of milk borne diseases.. Prioritising certain sub population at households (Pregnant women and children) makes then vulnerable to milk-borne hazards. It will be challenging to change the risky practices as they are motivated by cultural beliefs hence the best strategy to promote milk safety will be to encourage the boiling of milk by consumers.